Eyes of the city architecture and urban space after artificial intelligence - Ratti, Carlo 1971-; Bonino, Michele 1974-; Sun, Yimin ca. 20. Jh; Federighi, Valeria ca. 20. Jh; Naso, Monica ca. 20. Jh; Belleri, Daniele ca. 20. Jh (Hatje Cantz, 2021)
Digital devices gather real-time data about urban space with sensors, actuators, and artificial intelligence. We have entered the era of the "eyes of the city", when each of us must negotiate everyday life under their omnipresent gaze. Following up on the eponymous exhibition at the Bi-City Shenzen Biennale of Urbanism\Architecture 2019, this book examines the relationships between cities and digital technologies across various disciplines. As the Internet of Things dramatically expands its reach, touching upon critical issues including individual anonymity, data ownership, and design by proxy, how can designers, architects, and urban stakeholders see eye to eye with our artificial counterparts?